Adaptation of the Phubbing Scale and of the Generic Scale of Being Phubbed for the Portuguese population - Mendes, Letícia (2022)
Excessive, abusive, or inappropriate use of mobile phones can have a negative effect on interpersonal relationships. This study aims to adapt the Phubbing Scale (PS) and the Generic Scale of Being Phubbed (GSBP) for the Portuguese population, establishing the convergent validity of the instruments with others that assess approximate constructs, such as the Partner Phubbing Scale (PPS)and the Nomophobia Questionnaire (NMP-Q), and investigate the differences and/or relationships between sociodemographic variables, mobile phone usage variables and the PS and the GSBP. This is a cross sectional study, including 641 participants, aged between 18-71 (M=27.91; SD=10.60). The Portuguese version of the PS kept the number of items and factors, however, distributed differently from the original version. The Portuguese version of the GSBP kept the structure proposed by the authors of the original version. The correlations obtained by both scales with other instruments ensured convergent validity. Differences were found in the values of the scales according to some sociodemographic variables and some variables regarding mobile phone use. The findings provide culturally adapted and validated two instruments and are helpful to researchers to assess this phenomenon and intervene in a timely manner.